Conversion of a microwave synthesized alkali-metal MOF to a carbonaceous anode for Li-ion batteries - Desai, Aamod V; Pimenta, Vanessa; King, Cara; Cordes, David B; Slawin, Alexandra M Z; Morris, Russell E; Armstrong, A Robert (RSC advances, 2020)
Hierarchical carbon-rich materials have shown immense potential for various electrochemical applications. Metal-organic frameworks (MOFs) are well suited precursors for obtaining such templated carbon matrices. Usually these conversions are carried out by energy intensive processes and lead to the presence of toxic transition metal residues. Herein, we demonstrate the green, scalable, microwave-assisted synthesis of a three-dimensional s-block metal based MOF and its efficient transformation into a carbonaceous material. The MOF-derived solid functions as a negative electrode for lithium-ion batteries having moderate low-rate capacities and cycling stability.